Artificial Intelligence in Health care and its application in Saudi Arabia - Aljerian, Nawfal; Arafat, Mohammad; Aldhubib, Abdulrahman; Almohaimeed, Ibrahim; Alsultan, Ali; Alhosaini, Abdulaziz; Aloqayli, Ahmed; AlRabiah, Bader; AlBanyan, Sara; Bin Ashry, Lyla; et al. (International Journal of Innovative Research in Medical Science, 2022)
Background In recent years, the utilization of Artificial Intelligence (AI) has increased dramatically with the launch of vision 2030 in Saudi Arabia (SA). Vision 2030 is a quality-driven mission set to make SA one of the most efficient countries in healthcare. SA has launched several initiatives for the national digitalization mission. The Saudi Data and Artificial Intelligence Authority (SDAIA) has been established for that purpose, other entities including the National Healthcare Command and Control Center (NHCCC). The most successful and promising application of AI so far is in diagnostic radiology and conceptualizing a personalized health plan. With the current trend in precision medicine, AI will be a valuable asset in producing an individualized healthcare plan. The potential for AI has been amplified throughout the Covid-19 pandemic and has accelerated the agenda for an immediate execution plan. In each phase of the pandemic, AI has been integral to identifying novel strains of the virus, undergoing containment measures, and assisting in the public’s adherence to them. This review explores the potential of AI in healthcare, its drawbacks, and the role of AI in the national health transformation mission launched by SA. Despite the potential of AI in healthcare, it has significant limitations, mainly the lack of institutional resources and inadequate training of healthcare workers. Summary The potential of AI is nearly limitless, but only a fraction of its capabilities have been explored. SA has launched several initiatives to utilize AI in healthcare, including multiple health mobile apps, telemedicine, and electronic medical health records. These initiatives formed a cornerstone in helping SA handle the pandemic more efficiently.